Autoantibodies against eukaryotic translation elongation factor 1 delta in two patients with autoimmune cerebellar ataxia - Guo, Liyuan; Ren, Haitao; Fan, Siyuan; Chao, Xingchen; Liu, Mange; Guan, Hongzhi; Wang, Jing (Frontiers in Immunology, 2024)
Background: Autoantibodies are useful biomarkers for the early detection and diagnosis of autoimmune cerebellar ataxia (ACA).Objectives: To identify novel autoantibody candidates in ACA patients.Methods: Patients with cerebellar ataxia of unknown cause were recruited from July 2018 to February 2023. Anti-neural autoantibodies in patient samples were detected by tissue-based indirect immunofluorescence assay (TBA) on rat cerebellum sections. TBA-positive samples were further screened for well-established anti-neural autoantibodies by using commercial kits. Tissue-immunoprecipitation (TIP) and subsequent mass spectrometric (MS) analysis were used to explore the target antigen of autoantibodies in TBA-positive but known autoantibody-negative samples. The specific binding between autoantibodies and identified target antigen was confirmed by neutralization experiments, recombinant cell-based indirect immunofluorescence assay (CBA) and western blotting experiments.The eukaryotic translation elongation factor 1 delta (EEF1D) protein was identified as target antigen of autoantibodies in samples from an ACA patient, a 43year-old female, while the specific binding of autoantibodies and EEF1D was confirmed by subsequent experiments. The second anti-EEF1D autoantibody-positive ACA patient, a 59-year-old female, was detected in consequence screen. The main clinical manifestations of the two patients were cerebellar syndrome, such as unsteady walking and limb ataxia. Both patients received immunotherapy, including corticosteroids, intravenous immunoglobulin and mycophenolate mofetil. Their outcomes supported the effectiveness of immunotherapy, but the cerebellar atrophy that occurred before treatment may be irreversible.In the current study, we identified anti-EEF1D autoantibody as a novel autoantibody candidate in ACA. Its pathological roles and diagnostic value need to be further verified in larger-scale studies.